2019
DOI: 10.1371/journal.pone.0219853
|View full text |Cite
|
Sign up to set email alerts
|

Trends in reported malaria cases and the effects of malaria control in the Democratic Republic of the Congo

Abstract: Background Considerable upscaling of malaria control efforts have taken place over the last 15 years in the Democratic Republic of Congo, the country with the second highest malaria case load after Nigeria. Malaria control interventions have been strengthened in line with the Millenium Development Goals. We analysed the effects of these interventions on malaria cases at health facility level, using a retrospective trend analysis of malaria cases between 2005 and 2014. Data were collected from outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…The latter intervention improved the availability of RDTs at the community level [8,9]. The effect of the introduction of malaria RDT on the number of tested and confirmed cases is in line with the result of a study carried out in the Democratic Republic of the Congo in 2017 [15].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The latter intervention improved the availability of RDTs at the community level [8,9]. The effect of the introduction of malaria RDT on the number of tested and confirmed cases is in line with the result of a study carried out in the Democratic Republic of the Congo in 2017 [15].…”
Section: Discussionmentioning
confidence: 62%
“…In this study, we used routinely collected data to explore, firstly, the spatio-temporal pattern of malaria (suspected, tested, and confirmed) between 2013 and 2018, and secondly, to assess the effect of the free-of-charge health care policy on malaria reported cases incidence in Burkina Faso. Most studies in this field focused on the effects of interventions, such as ITNs, malaria diagnosis, and treatment, and our study is the first to provide evidence on the associations between the free-of-charge health care policy for children under five and malaria morbidity [15,38,[43][44][45].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, TCM is directly dependent on access to care and diagnositc testing and therefore highly susceptible to bias by these factors. For example, in a study from the Democratic Republic of the Congo evaluating trends in reported malaria cases between 2005 and 2014, a sharp increase in con rmed cases after 2010 was presumed to be due to the introduction and scale up in RDTs rather than a true increase in the incidence of malaria [25]. The study presented in this report bene ted from an enhanced surveillance system where almost all patients with suspected malaria underwent diagnostic testing using an RDT.…”
Section: Discussionmentioning
confidence: 97%